Optimization of the quality indicators of co-ordinated the size of holes in the machining - Пащенко, Едуард Андрійович; Тріщ, Галина Михайлівна (Eastern-European Journal of Enterprise Technologies, 2012)
Experiment planning to find optimal conditions for producing holes in various materials is carried out. The dependences for the practical of the stray fields of sizes from the base and the positional deviations of the axes of holes are given